Relationship between Biology Education Students' Learning Period and Grade Point Average (GPA) - Muhammad Rafik; Annisa Fitri Kamilah; Fatmalariasari Fatmalariasari; Rosdiana Rosdiana; Siti Komariah; Indah Juwita Sari; Suppamai Promkaew (International Journal of Biology Education Towards Sustainable Development, 2023)
The grade point average (GPA) is the value obtained by students cumulatively from the beginning to the end of the semester. To get a high GPA, students must study hard. Learning period is not a guarantee of getting a high GPA. The problem that is now happening is how students use learning time effectively so that their learning results are maximized. This research aimed to know the relationship between the learning period and GPA. The type of research used is quantitative correlational research to know the relationship between the learning period and GPA. The subjects in this study were 33 students at the fifth semester in the Department of Biology Education at a public university in Indonesia. The research implementation phase included data collection, data analysis, and conclusion. The results of the simple correlation test analysis of Spearmann Correlation Kendall's tau-b show that r count r table (0.139 0.442) on the Kendall's tau-b test, r count r table (0.168 0.442) on the Spearmann rho test, and the R-value is 19.1 which states that the relationship between the learning period and GPA results is low. This study concludes that there is no relationship between the learning period and the grade point average (GPA) of the biology education students. The absence of this relationship can be influenced by several factors, such as school factors, family factors, the inability to determine the priority scale of planned activities, as well as factors of interest and motivation to learn.